2010
DOI: 10.1002/chir.20868
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective desymmetrization of meso‐epoxides with anilines catalyzed by polymeric and monomeric Ti(IV) salen complexes

Abstract: The active catalysts for the enantioselective ring opening (ARO) of meso-stilbene oxide, cis-butene oxide, cyclohexene oxide, cyclopentene oxide, and cyclooctene oxide with various substituted anilines were generated in situ by the reaction of Ti(O(i)Pr)(4) with poly-[(R,R)-N,N'-bis-{3-(1,1-dimethylethyl)-5-methylene salicylidene} cyclohexane-1,2-diamine]-1 and (1R,2R)-N,N'-bis[3,5-di(tert-butyl)salicylidene] cyclohexane-1,2-diamine-2. These catalysts in the presence of nonracemic imine as an additive provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The results are given in Figure 3. In our initial screening of Al III catalysts, we have used monomer,17 dimer,18a polymer,18b salalen (half reduced salen),18c salan (reduced salen),18d and amino alcohol based ligands 18e. We observed that the chiral monomeric Al III salen complex is an effective catalyst in terms of reactivity and enantioinduction (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results are given in Figure 3. In our initial screening of Al III catalysts, we have used monomer,17 dimer,18a polymer,18b salalen (half reduced salen),18c salan (reduced salen),18d and amino alcohol based ligands 18e. We observed that the chiral monomeric Al III salen complex is an effective catalyst in terms of reactivity and enantioinduction (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Kureshy and coworkers [55,56] investigated several different approaches to achieve the enantioselective synthesis of vicinal amino alcohols by the ARO of meso-epoxides. One such approach is the use of in situ generated monomeric and polymeric Ti(IV)salen complexes from ligands 32 and 33 (Scheme 9) [55]. In order to achieve an efficient asymmetric catalysis, high catalyst loading (20 mol%) and the addition of additives was required.…”
Section: With Anilines Amines and Carbamatesmentioning
confidence: 99%
“…Chiral metal–salen complexes were designed for catalyzing reaction processes that resulted in good yield, high regioselective and enantioselective control for the asymmetric ring opening of terminal epoxides. Various metals have been explored to optimize the catalytic properties of chiral metal–salens, such as Cr [ 7 ], Co [ 8 ], Fe [ 9 ], Ti [ 10 ], Al [ 11 ], Y [ 12 ], and Mn [ 13 ] and investigated with numerous nucleophiles to afford chiral molecules. In addition to the variation of metals, salen ligands have also been studied with regard to conformational differences, for instance, oligosalen [ 14 ], macrocyclic oligosalen [ 15 ], and polymeric salen [ 16 ].…”
Section: Introductionmentioning
confidence: 99%